1988
DOI: 10.4278/0890-1171-3.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Worksite Self-Help Smoking Cessation Program for Registered Nurses

Abstract: Cigarette smoking among nurses remains a public health concern despite a recent decline in current smoking prevalence. We recruited 149 registered nurses into a no-cost, targeted, self-help smoking cessation program supplemented by a supportive worksite environmental module. The study was designed to expand understanding of nurses' smoking and to measure program effectiveness. Follow-ups were conducted at one, six and 12 months post-intervention to assess self-reported smoking status (92% objectively validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
5
29
0
3
Order By: Relevance
“…Although nurses have contributed to the knowledge of the morbidity and mortality caused by tobacco use among women through their participation in the Nurses Health Study (US Department of Health and Human Services, 2001), there have been limited efforts to assist nurses with smoking cessation (Chalmers et al, 2001;Gritz et al, 1988;Rowe & Clark, 1999). One research group (Gritz et al, 1988), in a study of nurses' workplace smoking and quitting (n ¼ 149 in 15 acute care hospitals in Los Angeles, reported a 12.7% point prevalence quit rate at 12 months. Chalmers et al (2001) conducted an 8-week support group, community-based intervention for Canadian nurses (n ¼ 217).…”
Section: Interventions To Help Nurses Quit Smokingmentioning
confidence: 99%
See 3 more Smart Citations
“…Although nurses have contributed to the knowledge of the morbidity and mortality caused by tobacco use among women through their participation in the Nurses Health Study (US Department of Health and Human Services, 2001), there have been limited efforts to assist nurses with smoking cessation (Chalmers et al, 2001;Gritz et al, 1988;Rowe & Clark, 1999). One research group (Gritz et al, 1988), in a study of nurses' workplace smoking and quitting (n ¼ 149 in 15 acute care hospitals in Los Angeles, reported a 12.7% point prevalence quit rate at 12 months. Chalmers et al (2001) conducted an 8-week support group, community-based intervention for Canadian nurses (n ¼ 217).…”
Section: Interventions To Help Nurses Quit Smokingmentioning
confidence: 99%
“…In the current health care climate, nursing is a valued, but stressful occupation (American Nurses Association, 2002), with many nurses working 12-hour shifts. The evidence for the association of stress in the workplace and smoking among nurses has been inconsistent, yet stress has been cited as a barrier to their ability to quit (Berman, Read, Marcus, & Gritz, 1992;Gritz et al, 1988;McKenna et al, 2003). Lack of support from co-workers has been identified in some studies as a reason for fewer quit attempts Bramadat et al, 1999;Gritz et al, 1988;Rowe & Macleod-Clark, 2000).…”
Section: Workite Issues Related To Smokingmentioning
confidence: 99%
See 2 more Smart Citations
“…Gritz et al (1988) reported a work-site oriented, self-help intervention with 149 registered nurses, based on the use of the American Lung Association manuals. Gritz et al (1988) reported a work-site oriented, self-help intervention with 149 registered nurses, based on the use of the American Lung Association manuals.…”
Section: Intervention Programsmentioning
confidence: 99%